(untitled) (Journal of Misan Researches, 2025)
The city of Jaffa is located on the eastern shore of the Mediterranean Sea, to the northwest of the city of Jerusalem (Al-Quds Al-Sharif), and it was a district center affiliated with the Al-Quds Al-Sharif Province, directly affiliated to the Sublime Porte in Istanbul. This research aims at showing an aspect of the role of women in the social and economic life in the community of the city of Jaffa in the late Ottoman era. The endowment document included important information about the social and economic life in Jaffa. This research is based entirely on a document or endowment argument by Hajja Khadija Umm Rabah, daughter of Sheikh Salim son of Sheikh Salama Al-Dajjani. The document dates back to Muharram 17, 1319 AH/1901 AD, and it is preserved in the records of the Jaffa Sharia Court. Keywords: endowment, Jaffa city, Jaffa Sharia Court.